Miliary tuberculosis with positive acid-fast bacilli in a pediatric patient - Fernandes, Sara Regina Castanheira; Homa, Marcia Noriko de Oliveira; Igarashi, Aghata; Salles, Andréa Luiza Mendes; Jaloretto, Ana Paula; Freitas, Maria Silvia; Nogueira, Paulo Cesar Koch (São Paulo Medical Journal, 2003)
CONTEXT: Tuberculosis is an important public health issue. The Brazilian government reported 78,460 new cases in 1999. Miliary tuberculosis is a severe form of this disease. OBJECTIVE: To report on an uncommon clinical presentation of miliary tuberculosis in a child. CASE REPORT: A 5-year old boy presented in the emergency room with fatigue and weight loss. He had had Staphylococcus aureus pneumonia 7 months before. Chest radiography revealed lobar consolidation and miliary pattern associated with small cavities in both upper lobes. Antibiotic therapy was started. The sputum was positive for acid-fast bacilli and hence the treatment recommended for tuberculosis (rifampicin, isoniazid [INH], pyrazinamide) was started. The patient was treated for 9 months and at the end of the follow-up period he had made a complete clinical recovery. CONCLUSION: Although in some particular cases sputum can be positive for acid-fast bacilli in children, limitations to the sputum test have forced pediatricians to base tuberculosis diagnosis on epidemiological data, clinical findings and radiographic pattern. In this particular case, we hypothesize that the sputum bacillus test was positive because bacilli grew inside residual pneumatoceles that were produced during previous pneumonia.